I.
II. 2sinx-cos^2x*sinx=0
sinx(2-cos^2x)=0
1)sinx=0
x=pik . k=z
2)2-cos^2x=0
cos^2x=2
cosx=+-√2
x=+-arccos(+-√2)+2pik . k=z
2sinx-cos^2x*sinx=0
x=πk, k∈Z
cosx=±√2
x=±arccos(±√2)+2πk, k∈Z
I.![y=\frac{6-x}{3x+1}\\OD3:3x+1\neq0\\x\neq-\frac{1}{3}\\D(y)=(-\infty;-\frac{1}{3})U(-\frac{1}{3};+\infty)](/tpl/images/0120/5920/19e72.png)
II. 2sinx-cos^2x*sinx=0
sinx(2-cos^2x)=0
1)sinx=0
x=pik . k=z
2)2-cos^2x=0
cos^2x=2
cosx=+-√2
x=+-arccos(+-√2)+2pik . k=z
2sinx-cos^2x*sinx=0
sinx(2-cos^2x)=0
1)sinx=0
x=πk, k∈Z
2)2-cos^2x=0
cos^2x=2
cosx=±√2
x=±arccos(±√2)+2πk, k∈Z